IMPLEMENTATION OF BUILDING LEARNING POWER (BLP) AS AN EFFORT TO STRENGTHEN QUR'ANIC CHARACTER IN THE DIGITAL ERA: CASE STUDY IN MUHAMMADIYAH EDUCATIONAL ENVIRONMENT - Jannah, Miftahol; Humaidi, M. Nurul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This study aims to examine the implementation of Building Learning Power (BLP) as an effort to strengthen Qur'anic character in the digital era at Muhammadiyah educational institutions. This strategy is a very relevant approach to the development of education based on Islamic (religious) values. Building Learning Power (BLP) is a learning strategy concept introduced by Guy Claxton, focusing on the development of in-depth learning skills, including resilience/perseverance, critical thinking skills, creativity, and the ability to work together. This study uses a qualitative approach with case studies at Muhammadiyah educational institutions in Sidoarjo. Research data were obtained through observation, interviews and documentation studies. The research findings show that the application of the Building Learning Power (BLP) concept can improve the quality of Qur'anic character amidst the flow of digital era disruption that continues to develop massively. The emphasis on values ​​such as resilience, perseverance, honesty, independence, critical thinking and cooperation are forms of implementation of the values ​​of piety that are highly emphasized in the Qur'an. This research is expected to be able to contribute to the development of character-based education curriculum based on the principles of Islamic teachings in the digital era. Keywords: Building Learning Power, Qur'anic Character and Digital Era